Policies and Effectiveness of Foreign Aid: The Case of Sri Lanka - Bhavan, T. (Asian Economic and Financial Review, 2013)
This empirical study investigates foreign aid’s effectiveness in stimulating growth by considering economic policies and the factors that influenced aid flow in Sri Lanka during the period of 1980-2008. For both analyses, a single-equation instrumental variable estimation method is employed. The results derived from this study suggest that aid is positively associated with growth in a good policy environment in Sri Lanka. Regarding determinants, in terms of trade openness and budget deficits the results suggest that aid was transferred into Sri Lanka under a conditional policy environment. Inflation is positively associated with aid flow. Unrest in the country and per capita growth negatively influenced aid, whereas commercial interests, natural disasters, political stability, and poverty are positively associated with aid inflow.